2004
DOI: 10.1079/pns2003315
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the nutritional biochemistry of trivalent chromium

Abstract: The nutritional biochemistry of trivalent Cr has been a poorly understood field of study; investigations of the biochemistry of the other essential transition metals have not proven as problematic. Despite over four decades of endeavour, only recently has a picture of the role of Cr potentially started to be defined. The biologically-relevant form is the trivalent ion. Cr3+appears to be required for proper carbohydrate and lipid metabolism in mammals, although fortunately Cr deficiency is difficult to achieve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 76 publications
4
104
2
3
Order By: Relevance
“…Trivalent chromium (Cr) is an essential trace element for human and animal nutrition (Mertz, 1993) and enhances insulin function in the form of a low molecular weight Cr binding substance (LMWCr), called chromodulin (Vincent, 2004). Severe Cr deficiency induces impaired glucose tolerance and is believed to increase the risk for diabetes (Mertz, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent chromium (Cr) is an essential trace element for human and animal nutrition (Mertz, 1993) and enhances insulin function in the form of a low molecular weight Cr binding substance (LMWCr), called chromodulin (Vincent, 2004). Severe Cr deficiency induces impaired glucose tolerance and is believed to increase the risk for diabetes (Mertz, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The major factor that causes Cr(III) to be regarded as an essential element is its purported function in carbohydrate and lipid metabolism through its interaction with insulin [1][2][3][4]. However, the acceptance of Cr(III) as an essential element for humans and animals is now widely controversial since specific chemical mechanisms and the biologically active form by which Cr(III) carries out its insulin potentiating activities has not been found yet [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have questioned the safety of certain supplemental trivalent Cr complexes (26). Comparative studies of chromium(III) picolinate and niacin-bound chromium(III), two popular dietary supplements, have revealed that chromium(III) picolinate produces significantly more oxidative stress and DnA damage (27)(28)(29)(30). Recently, chromium picolinate has been shown to be mutagenic in some in vitro tests, and picolinic acid moiety appears to be responsible for that effect (27) 3 ] + cation has been studied and proposed as an alternative supplemental source of Cr.…”
Section: Evaluation Of Insulin Binding and Signaling Activity Of Newlmentioning
confidence: 99%